Pengaruh Desain dan Inovasi Produk Terhadap Brand Love, Purchase Decision, dan Brand Loyalty Jersey Manchester United - Pengestu, Kantri Setiawan; Tuti, Meylani (Catalist Indo Publisher, 2025)
This study investigates the influence of product design and innovation on brand love, purchase decisions, and brand loyalty among consumers of Manchester United jerseys. Employing a quantitative approach, data were collected from 250 respondents through an online survey and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that both product design and innovation significantly affect brand love. Furthermore, brand love exerts a strong influence on purchase decisions and brand loyalty. Purchase decisions also have a significant and direct impact on brand loyalty. These findings suggest that emotional attachment, reflected in brand love, plays a pivotal role in shaping consumer behavior, particularly in repeated purchases of identity-related products such as football jerseys. From a practical standpoint, the study highlights the importance for brands to invest in creative design and continuous innovation to foster stronger emotional connections and long-term consumer loyalty.